Potential of traditional medicinal plants in the Dayak Tamambaloh Tribe, West Kalimantan, Indonesia - MARKUS IYUS SUPIANDI; HENDRIKUS JULUNG; YUDITA SUSANTI; SITI ZUBAIDAH; SUSRIYATI MAHANAL (Society for Indonesian Biodiversity, 2023)
Abstract. Supiandi MI, Julung H, Susanti Y, Zubaidah S, Mahanal S. 2023. Potential of traditional medicinal plants in the Dayak Tamambaloh Tribe, West Kalimantan, Indonesia. Biodiversitas 24: 3384-3393. The Dayak tribe in West Kalimantan (Indonesia) consists of 151 sub-ethnics, one of which is the Dayak Tamambaloh located in Temau Village, Embaloh Hulu Subdistrict, Kapuas Hulu District, West Kalimantan, Indonesia. This tribe uses the forest for various purposes, including plants as traditional medicines, which is a form of local wisdom in the community. However, the local wisdom can be threatened with extinction when it is not preserved properly. Factors contributing to the extinction of local wisdom include the influence of foreign cultures, forest degradation due to shifting cultivation, the existence of oil palm plantations, and forest fires. Therefore, this study aimed to examine the use of plants as traditional medicine with a qualitative descriptive approach. The method used was a survey; data were obtained from the key informants. They are knowledgeable about the uses of plants for traditional medicine. Data on medicinal plants were collected through in-depth interviews, field observations, documentation, and were then analyzed descriptively and qualitatively. The results showed that the plants used to treat diseases by the Dayak Tamambaloh tribe were 58 and consisted of 29 families. The most widely used families were Zingiberaceae, Euphorbiaceae, Lamiaceae, Poaceae, and Musaceae, with 10, 4, 4, 4, and 3 species, respectively.